2016
DOI: 10.7326/m15-2152
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Use of Low-Value Health Care Services Among U.S. Advanced Practice Clinicians and Physicians

Abstract: Background Many physicians believe that advanced practice clinicians (APCs [nurse practitioners and physician assistants]) provide care of relatively lower value. Objective To compare use of low-value services among U.S. APCs and physicians. Design Service use after primary care visits was evaluated for 3 conditions after adjustment for patient and provider characteristics and year. Patients with guideline-based red flags were excluded and analyses stratified by office-versus hospital-based visits, acute v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 36 publications
3
57
1
Order By: Relevance
“…APPs are viewed as a key component of primary care delivery, in which substantial data suggests that APPs provide care equivalent in quality to MDs . A randomized controlled trial comparing nurse practitioners practicing independently versus physicians in primary care showed no differences in mortality or other important health outcomes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…APPs are viewed as a key component of primary care delivery, in which substantial data suggests that APPs provide care equivalent in quality to MDs . A randomized controlled trial comparing nurse practitioners practicing independently versus physicians in primary care showed no differences in mortality or other important health outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with cirrhosis are not co‐managed by a gastroenterology‐trained or hepatology‐trained specialist . Previous studies have demonstrated that advanced practice providers (APPs) provide care that is equivalent in quality to medical doctors (MDs) in both primary care and specialty care when their practice is focused on one condition . However, data are lacking regarding quality metric performance for APPs in patients with cirrhosis.…”
mentioning
confidence: 99%
“…Missing data are rare (e.g., answers to the survey question, “Have you or anyone in this practice seen this patient before?” are missing 2.9% of the time), and multiple imputation techniques are used for missing data. 1 …”
Section: Methodsmentioning
confidence: 99%
“…1,15 Based on prior research, we chose three episodic conditions that are frequently associated with low value care: (1) upper respiratory infections (URIs, such as acute bronchitis and pharyngitis), (2) back pain, and (3) headache, which are commonly treated by generalists or in general medical clinics and based on prior research. 1,6,7 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation